The Oxford handbook of stress and mental health - Harkness, Kate L.; Hayden, Elizabeth P. (Oxford, (UK): Oxford University Press, 2020)
"Virtually all mental disorders show associations with stressful life events. Because of the ubiquity of stress in mental health problems, students, clinicians, and scientists in relevant fields require a broad understanding of stress assessment, the factors that influence how impactful a given stressor is on an individual, how the role of stress varies across different disorders, and treatments for stress-related problems. This handbook provides an in-depth, comprehensive overview of these key issues in the field of stress and mental health via chapters written by internationally acclaimed experts from an array of disciplines and scientific traditions, all of whom are concerned with understanding how stress impacts mental health"--
Includes bibliographical references and index.
Keywords: Stress management -- Handbooks, manuals, etc; Stress (Psychology) -- Treatment; Mental illness -- Treatment